THE ROLE OF INSTITUTIONAL OWNERSHIP, INDEPENDENT BOARD OF COMMISSIONERS, AND MANAGERIAL OWNERSHIP ON EARNINGS MANAGEMENT IN MANUFACTURING COMPANIES - Endah Prawesti Ningrum (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This research purpose to assign the clout of institutional possession, self-sustained board of commissioners and managerial possession on income management with manager bonuses in manufacturing companies registered on the Indonesian stock exchange in the 2016-2018 period. The sample selection was conducted using purposive sampling technique. The sample amounted to 59 companies with a 3 year period. The method using descriptive analysis and confirmation. The confirmation analysis uses panel data regression analysis (pooled data). The data processing tool uses Eviews 9. The inference of this reseacrh is that institutional possession has a significant influence on income management, bonus managers cannot moderate the effect of institutional possession on income management, this self-sustained board of commissioners has a significant influence on income management, Bonus manager cannot moderate the effect of the self-sustained board of commissioners on income management and managerial possession has a significant effect on income management.